PENGEMBANGAN MODUL DENGAN MODEL INKUIRI TERBIMBING BERBASIS LITERASI SAINS PADA MATERI SISTEM PEREDARAN DARAH PADA MANUSIA BAGI SISWA KELAS VIII SMP - Setiawati, Ratih; Natalina, Mariani; Darmadi, Darmadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to produce modules with guided inquiry models based on quality scientific literacy. This research was carried out in the Biology Education Laboratory of the Faculty of Teacher Training and Education, University of Riau and the state junior high school 4 Pekanbaru in April-October 2019. The type of researchused is Research and Development (R&D). Module development implemented refers to the ADDIE model with the stages of Analyze, Design, Development, Implementation, Evaluation. This research was only carried out until the Development stage by conducting validation by a validator and a limited trial phase I by Biology Education Students of Teaching and Education Faculty of University of Riau, and a limited trial phase II by students of state junior high school 4 Pekanbaru. The assessment of the developed modules includes 5 aspects, namely the module format and graphic aspects, presentation techniques, the syntax of guided inquiry models, indicators of scientific literacy dimensions, and language assessment. The results of the average validation with the scientific inquiry based guided inquiry model was gained a score of 3.58 with a very valid category. The average results of the limited trials phase I and II was gained a score of 3.67 with a very good category. Based on these data it can be concluded that the modules with guided inquiry models based on science literacy that have been developed arecategorized as quality modules and can be used on a wide scale.KeyWords: Modules, Guided Inquiry Models, Scientific Literacy